BARRIERS AND FACILITATORS TO NURSE TECHNICIAN ADOPTION OF EVIDENCE-BASED PRACTICE: A MIXED METHODS STUDY - Mohmmed Rashed Al Mouteri, Farhan Rakan Alanazi, Nawaf Saad Almutairi, Jassim Mohammad Alshammari, Abdulaziz Fadhel Alshammari, Dhaidan Saud Alshammari (Chelonian Research Foundation, 2022)
Evidence-based practice, defined as the conscientious use of current best evidence in clinical decision making, has well-established benefits for enhancing quality of care and patient outcomes. However, research indicates adoption of evidence-based protocols remains suboptimal among nurse technicians working in hospital settings. This explanatory sequential mixed methods study aimed to identify barriers and facilitators influencing nurse technician utilization of evidence-based practice in three public hospitals in Saudi Arabia to inform tailored organizational and educational strategies for promoting adoption. In the quantitative phase, a cross-sectional survey of 121 nurse technicians assessed perceptions regarding evidence-based practice barriers and facilitators. Insufficient time, knowledge, training, and protocol access emerged as the top barriers, while education programs, mentorship, and nursing leadership support were identified as key facilitators. The qualitative phase involved focus groups with 15 nurse technicians to provide in-depth understanding of challenges to evidence-based practice. Major themes highlighted workflow constraints, knowledge deficits, and organizational barriers including inadequate access to evidence-based protocols and decision supports as factors hindering adoption. Addressing modifiable barriers through a multifaceted approach encompassing strategies such as implementation of tailored educational programs, evidence-based protocol integration in electronic records, mentorship programs, workflow restructuring to enable literature searching, and optimizing technology access and training is crucial for facilitating nurse technician utilization of evidence-based practice. Findings provide crucial insights to inform organizational priorities and initiatives aimed at promoting nurse technician adoption of evidence-based protocols to provide the highest quality of empirically supported care.